1999
DOI: 10.1111/j.1468-3083.1999.tb01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐dermal elastolysis associated with Hashimoto's thyroiditis

Abstract: We report the case of a 38-year-old Caucasian female presenting asymptomatic plaques of fine wrinkling and perifollicular papular protrusions especially on the trunk. Histological examination evidenced loss of elastic fibers in the mid-dermis due to elastophagocytosis, with giant cells and granuloma formation. Moreover, elevated titers of thyroid autoantibodies were detected and thyroid ultrasound revealed echo-poor tissue. These findings met the diagnoses of mid-dermal elastolysis and Hashimoto's thyroiditis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Gambichler et al found increased histiocyte activity—the natural producer of MMPs—in MDE lesions as well as objective upregulation of MMPs and elastophagocytosis. This is accompanied by downregulation of tissue inhibitor of metalloproteinase 1, which is responsible for the physiological negative feedback of MMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambichler et al found increased histiocyte activity—the natural producer of MMPs—in MDE lesions as well as objective upregulation of MMPs and elastophagocytosis. This is accompanied by downregulation of tissue inhibitor of metalloproteinase 1, which is responsible for the physiological negative feedback of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 These peptidases are naturally responsible for extracellular matrix degradation; overactivity causes pathologic elastin destruction and therefore decreased skin resilience and wrinkling. 3 Gambichler et al 1,4 found increased histiocyte activitythe natural producer of MMPs-in MDE lesions as well as objective upregulation of MMPs and elastophagocytosis. This is accompanied by downregulation of tissue inhibitor of metalloproteinase 1, which is responsible for the physiological negative feedback of MMPs.…”
Section: Observation Middermal Elastolysis-a Possible End Stage Of Gr...mentioning
confidence: 99%